61.5.12 problem 12

Internal problem ID [12136]
Book : Handbook of exact solutions for ordinary differential equations. By Polyanin and Zaitsev. Second edition
Section : Chapter 1, section 1.2. Riccati Equation. subsection 1.2.4-1. Equations with hyperbolic sine and cosine
Problem number : 12
Date solved : Tuesday, January 28, 2025 at 12:29:52 AM
CAS classification : [_Riccati]

\begin{align*} 2 y^{\prime }&=\left (a -\lambda +a \cosh \left (\lambda x \right )\right ) y^{2}+a +\lambda -a \cosh \left (\lambda x \right ) \end{align*}

Solution by Maple

Time used: 0.005 (sec). Leaf size: 101

dsolve(2*diff(y(x),x)=(a-lambda+a*cosh(lambda*x))*y(x)^2+a+lambda-a*cosh(lambda*x),y(x), singsol=all)
 
\[ y = \frac {\tanh \left (\frac {\lambda x}{2}\right ) \lambda \left (\int {\mathrm e}^{\frac {a \cosh \left (\lambda x \right )}{\lambda }} \left (-2 a +\operatorname {sech}\left (\frac {\lambda x}{2}\right )^{2} \lambda \right )d x \right ) c_{1} +2 \operatorname {sech}\left (\frac {\lambda x}{2}\right )^{2} {\mathrm e}^{\frac {a \cosh \left (\lambda x \right )}{\lambda }} c_{1} \lambda -2 \tanh \left (\frac {\lambda x}{2}\right )}{\lambda \left (\int {\mathrm e}^{\frac {a \cosh \left (\lambda x \right )}{\lambda }} \left (-2 a +\operatorname {sech}\left (\frac {\lambda x}{2}\right )^{2} \lambda \right )d x \right ) c_{1} -2} \]

Solution by Mathematica

Time used: 16.686 (sec). Leaf size: 338

DSolve[2*D[y[x],x]==(a-\[Lambda]+a*Cosh[\[Lambda]*x])*y[x]^2+a+\[Lambda]-a*Cosh[\[Lambda]*x],y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \frac {\text {sech}^2\left (\frac {\lambda x}{2}\right ) \left (c_1 \sinh (\lambda x) \int _1^x-e^{\frac {2 a \cosh ^2\left (\frac {1}{2} \lambda K[1]\right )}{\lambda }} (\cosh (\lambda K[1]) a+a-\lambda ) \text {sech}^2\left (\frac {1}{2} \lambda K[1]\right )dK[1]+4 c_1 e^{\frac {2 a \cosh ^2\left (\frac {\lambda x}{2}\right )}{\lambda }}+\sinh (\lambda x)\right )}{2+2 c_1 \int _1^x-e^{\frac {2 a \cosh ^2\left (\frac {1}{2} \lambda K[1]\right )}{\lambda }} (\cosh (\lambda K[1]) a+a-\lambda ) \text {sech}^2\left (\frac {1}{2} \lambda K[1]\right )dK[1]} \\ y(x)\to \frac {1}{2} \text {sech}^2\left (\frac {\lambda x}{2}\right ) \left (\frac {4 e^{\frac {2 a \cosh ^2\left (\frac {\lambda x}{2}\right )}{\lambda }}}{\int _1^x-e^{\frac {2 a \cosh ^2\left (\frac {1}{2} \lambda K[1]\right )}{\lambda }} (\cosh (\lambda K[1]) a+a-\lambda ) \text {sech}^2\left (\frac {1}{2} \lambda K[1]\right )dK[1]}+\sinh (\lambda x)\right ) \\ y(x)\to \frac {1}{2} \text {sech}^2\left (\frac {\lambda x}{2}\right ) \left (\frac {4 e^{\frac {2 a \cosh ^2\left (\frac {\lambda x}{2}\right )}{\lambda }}}{\int _1^x-e^{\frac {2 a \cosh ^2\left (\frac {1}{2} \lambda K[1]\right )}{\lambda }} (\cosh (\lambda K[1]) a+a-\lambda ) \text {sech}^2\left (\frac {1}{2} \lambda K[1]\right )dK[1]}+\sinh (\lambda x)\right ) \\ \end{align*}